Law and Rhetorics in Cicero Speech in Defence of Cnaeus Plancius - Nótári, Tamás (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
The speech in defence of Cnaeus Plancius was delivered in early autumn 54 B.C. Cn. Plancius won the office of aedilis of the year 54 by winning the election, and, as it was not rare in Rome, his competitor, who lost in the election, M. Iuventius Laterensis charged him of election bribery/fraud (ambitus). Defence was provided by Cicero, who—as was his custom—rose to speak as the last one. The close relation between Cicero and his defendant was highly influenced by the fact that Plancius, who acted in Macedonia as proquaestor, gave shelter to the exiled politician, which was equal to saving his life in the orator’s interpretation. Cicero responds to the allegations of general significance made by the prosecution, in not too exhaustive details, however, he turns the attention from the accused and his acts to his own person. After brief description of the historical background of the lawsuit, we analyse Pro Plancio more profoundly to investigate the rhetorical handling of the facts of the case, which will be compared to Pro Murena examined earlier at several points to ensure better understanding.